Quality of life/spirituality, religion and personal beliefs of adult and elderly chronic kidney patients under hemodialysis - Suzana Gabriela Rusa; Gabriele Ibanhes Peripato; Sofia Cristina Iost Pavarini; Keika Inouye; Marisa Silvana Zazzetta; Fabiana de Souza Orlandi (Universidade de São Paulo, 2014)
OBJECTIVE: to assess the quality of life of chronic kidney patients undergoing hemodialysis, using the WHOQOL-bref and WHOQOL-SRPB.METHOD: a descriptive and cross-sectional study was undertaken at a kidney replacement therapy service in the interior of the state of SP. The 110subjects who complied with the inclusion criteria answered the Subject Characterization Instrument, the WHOQOL-bref and WHOQOL-SRPB.RESULTS: most of the respondents were male (67.27%), with a mean age of 55.65 years, Catholic (55.45%), with unfinished primary education (33.64%) and without formal occupation (79.08%). The WHOQOL-bref domains with the highest and lowest mean score were, respectively, "psychological" (µ=74.20) and "physical" (µ=61.14). The WHOQOL-SRPB domains with the highest and lowest mean score were, respectively, "completeness and integration" (µ=4.00) and "faith" (µ=4.40).CONCLUSIONS: the respondents showed high quality of life scores, specifically in the dimensions related to spirituality, religion and personal beliefs. Losses were evidenced in the physical domain of quality of life, possibly due to the changes resulting from the chronic kidney disease and hemodialysis treatment.